Definitive Management Option of Pelvic Ring Injury - Mohammad Zaim Chilmi; Ismail Hadisoebroto Dilogo (Indonesian Hip and Knee Society (IHKS), 2021)
Pelvic ring injury is a rare condition with the incidence of hip fracture about 3% to 8% of all fractures. However, the majority of pelvic fracture patients have a high morbidity rate that could threaten their survival. The majority cause of hip fracture is high energy blunt trauma and is related to polytrauma incident. The main goals of management for pelvic ring injury are to restore the form and stability of the pelvic. The main goal is to prevent nonunion and malunion, which lead to chronic pain and disability. This review is focused on the strengths and weaknesses of the management option, approach and complication for pelvic ring fracture surgery. Complications of pelvic ring fracture surgery are bleeding, nerve damage, DVT, pulmonary embolism, soft tissue injury, sepsis, and malunion of the pelvis and nonunion. Management for pelvic ring fracture surgery is used based on the location and configuration of the fracture, implant availability, surgeon’s preference, and experience.